2022
DOI: 10.1007/jhep07(2022)072
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Kerr in the 2PM amplitude

Abstract: The classical scattering of spinning objects is well described by the spinor-helicity formalism for heavy particles. Using these variables, we derive spurious-pole-free, all-spin opposite-helicity Compton amplitudes (factorizing on physical poles to the minimal, all-spin three-point amplitudes) in the classical limit for QED, QCD, and gravity. The cured amplitudes are subject to deformations by contact terms, the vast majority of whose contributions we can fix by imposing a relation between spin structures — m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 96 publications
4
46
0
Order By: Relevance
“…Pushing beyond fourth order in spin, Ref. [67] gave a parametrization of a spurious-pole-free Compton amplitude, using the heavy-particle EFT formalism, while enforcing consistency with general principles and with the "minimal-coupling" (black-hole) 3-point ampitudes, and while conjecturally imposing a certain "black-hole spin structure" observed at lower orders (which for 2-to-2 amplitudes is equivalent to the "shift symmetry" posited in Ref. [57]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pushing beyond fourth order in spin, Ref. [67] gave a parametrization of a spurious-pole-free Compton amplitude, using the heavy-particle EFT formalism, while enforcing consistency with general principles and with the "minimal-coupling" (black-hole) 3-point ampitudes, and while conjecturally imposing a certain "black-hole spin structure" observed at lower orders (which for 2-to-2 amplitudes is equivalent to the "shift symmetry" posited in Ref. [57]).…”
Section: Introductionmentioning
confidence: 99%
“…[76], a promising approach 1 The quintic-in-spin Compton as constrained by requiring the best-behaved high-energy limit in Ref. [67] was shown there to be at odds with a Compton derived in Ref. [68] from a Lagrangian for a massive spin-5/2 particle which is uniquely determined by its 3-point satisfying "the current constraint" (known from higher-spin theory and necessary for the existence of an underlying unitary theory) and requiring a minimal number of derivatives in the coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[76][77][78][79] for recent reviews. Scattering amplitudes have now been applied for deriving a number of state-of-the-art predictions in the PM expansion (fixed order in G and all-orders in velocity), such as the 2-body Hamiltonian at 3PM [80,81] and 4PM [82,83], as well as for modeling spin [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100], tidal corrections [101][102][103][104][105][106], and radiative effects [107][108][109][110][111][112][113][114][115].…”
Section: Introductionmentioning
confidence: 99%
“…Complementary approaches have emerged to tackle this problem. One seeks to resolve the ambiguity in the classical regime, extrapolating patterns that emerged in the one loop conservative observables for low spin to higher spins [62][63][64]. For certain observables it was also shown that the details of the Compton amplitude can be ignored in the relevant regimes [58,65].…”
mentioning
confidence: 99%